Mass Collaboration and Learning: Structure and Methods - Zamiri, Majid (2022)
The rapid emergence of social networks and collaborative communities supported by the Internet and associated innovative technologies, and the increasing demand for continuous improvement and fostering lifelong learning have led to unprecedented waves of novelty in the ways people create and share knowledge in different spheres. In this regard, mass collaboration (MC) through Internet-based solutions has opened new windows of opportunity to collaborate massively and learn collectively in ways that seemed impossible even a few decades ago. Learning ecosystems can benefit from mass collaboration where large numbers of minds collectively drive intellectual efforts to learn in the form of knowledge building and sharing. Mass collaborative learning (MCL) is a new paradigm that represents a significant shift away from the traditional teacher-centered approach towards a self-directed model in virtual communities in which contributing members take on creative roles to maximize their learning and that of their peers. Furthermore, MCL provides greater opportunities for distributed contributors to engage in virtual global learning and take the advantage of powerful social communities of experts and counterparts. Even though MCL opens up an apparently limitless field for promoting social inclusion in effective learning, not all aspects, features, and characteristics of this phenomenon are quite clear and discovered at present. In order to design, implement, and exploit such a learning approach, influencing constituents should be identified, and appropriate conditions need to be provided. However, existing literature offers limited information, guidance, and support for the creation, operation, coordination, and development of MCL initiatives. In this context, there are a number of identified critical issues, specific problems, gaps, and inconsistencies, and this thesis is correspondingly conducted to propose a Meta-Governance framework for MCL initiatives (MGF-MCL). This framework, by benefiting from various other related ideas, models, and methods, tries to give further insights into an integrated perspective of the most complex concerning issues and also some internal and external aspects of governance for the MCL initiatives. Furthermore, the MGF-MCL intends to provide some directions, guidance, and support for the implementation, operation, and development of MCL initiatives. In this thesis work, in order to (a) guide our research endeavor, (b) concretize our research design, (c) design, develop, validate, and apply the MGF-MCL, and (d) understand the practical value of our findings, we have followed the design science research process (DSRP) approach. We have evaluated the validity and applicability of the MGF-MCL through a mix of methods namely, case studies in EU projects, peer-review publications, and an MCL illustration case. A number of scenarios made within the case studies have brought together several industry and academic experts to evaluate the validity and applicability of MGF-MCL. The peer reviews of contributed publications also assessed the quality of the work and helped to establish the validity of MGF-MCL based upon the expert knowledge of other researchers. The MCL illustration case provided empirical evidence, relying on observation and experimentation. In terms of research, the findings of our work offer direction and support for the creation, operation, and implementation of MLC initiatives.